PERUBAHAN LINGKUNGAN PENGENDAPAN HUBUNGANNYA DENGAN TEKTONIK KUARTER (Studi Kasus Geologi Kuarter di Wilayah Dataran Rendah Aluvial Hingga Pantai Sepanjang Maron- Sikucingkrajan, Kec. Gemuruh, Kab. Kendal (Jawa Tengah) - Poedjoprajitno, Soemantri; Moechtar, Herman; Hidayat, S. (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Quaternary deposits of the alluvial plain to coastal plains in the Kec. Gemuruh, Kabupaten Kendal in the north-coast of Java (The Central Java Province) have been studied. The study was based on an analyses of geological surface and subsurface, especially of six boreholes information obtained along the North-South, and the penetration of the bore head varied from 2.80 to 6,65 m. These Quaternary deposits, can be devided into Members of Sandstone Damar Formation (Tpds), Damar Formation (Qtd), floodbasin and river channel deposits. Based on the correlation of the lateral and vertical variations of the deposition environment in the eastern part, the sediment accumulations were recognised which are related to fault activities. Whereas, the sediment accumulations in the western part influenced by normal fault. The tectonic activities which controlled the deposition processes were recorded as two stages. These were, (1)the activity of uplift fault obtained along the West to East, (2)the activity of uplift with direction West to East in the northern part followed by activity of normal fault towards almost North-South. Relative sea-level changes affect coastal-plain environment, they are influenced by local tectonic and global of sea-level changes. The tectonic activity also would cause shallowing and steepening of the depositional slope. Keywords : Quaternary sediments, tectonic, structure geology, sediment accumulation